Biological invasions and human dimensions: We still need to work hard on our social perspectives - Alejandro Bortolus; Evangelina Schwindt (Ecología Austral, 2022)
In this article, we analyze and challenge a long-held paradigm that reduces the field of biological invasions to its ecological components. We explore thirteen case studies grouped within three major human dimensions (values, traditions, and quality of life) to show how biological invasions interwove and interact with them. The group of human dimensions we explore in this work, although small, exposes a rich spectrum of interdisciplinary synergies between natural and social sciences that should receive more attention to make the field of biological invasions more sound and socially integrated.